Answer:
Given expression [tex]4(x-3)+5x^{\bf -2}[/tex] for x=2 is
[tex]4(x-3)+5x^{\bf -2}=-\frac{\bf 11}{\bf 4}[/tex]
Step-by-step explanation:
Given expression is [tex]4(x-3)+5x^{-2}[/tex] for x=2
Let f(x) be the given expression
[tex]f(x)=4(x-3)+5x^{-2}[/tex]
now to find f(x) for x=2
ie., put x=2 in f(x) we get
[tex]4(x-3)+5x^{-2}=4(2-3)+5(2)^{-2}[/tex]
[tex]4(x-3)+5x^{-2}=4(-1)+5(2)^{-2}[/tex]
[tex]4(x-3)+5x^{-2}=-4+5\times \frac{1}{2}^}2}[/tex]
[tex]4(x-3)+5x^{-2}=-4+5\times \frac{1}{4}[/tex]
[tex]4(x-3)+5x^{-2}=-4+ \frac{5}{4}[/tex]
[tex]4(x-3)+5x^{-2}= \frac{-16+5}{4}[/tex]
[tex]4(x-3)+5x^{-2}= \frac{-11}{4}[/tex]
[tex]4(x-3)+5x^{-2}=-\frac{11}{4}[/tex]
Therefore the given expression [tex]4(x-3)+5x^{-2}[/tex] for x=2 is
[tex]4(x-3)+5x^{-2}=-\frac{11}{4}[/tex]